Rotor shape design of an interior PM type BLDC motor for improving mechanical vibration and EMI characteristics. - Hur, Jin (Journal of electrical engineering & technology)
This paper presents the rotor shape optimization of an interior type permanent magnet (IPM) motor for a reduction of vibration and electromagnetic interference (EMI). The vibration and EMI in permanent magnet motors isi generated by cogging torque ripple, radial force and commutation torque ripple. Consequently, in order to improve vibration and EMI, the optimal notches are put on the rotor pole with an arc shape proposed. The variation of vibration frequency due to the cogging torque and radial force of each model is computed by the finite element method (FEM). From the analysis result and experiment, we confirmed the proposed model has remarkably improved the vibration and EMI.